Risk factors for fatal and nonfatal repetition of suicide attempts: a literature review - Beghi M (Dove Medical Press, 2013)
Massimiliano Beghi,1,2 Jerrold F Rosenbaum,3 Cesare Cerri,1,4 Cesare M Cornaggia1,51Psychiatry Clinic, University of Milano Bicocca, Milan, Italy; 2Department of Psychiatry, Salvini Hospital, Rho, Italy; 3Massachusetts General Hospital, Harvard Medical School, Boston, MA, USA; 4Department of Rehabilitation Medicine, Zucchi Clinical Institute, Carate Brianza, Italy; 5Forensic Psychiatric Hospital, Castiglione delle Stiviere, Mantua, ItalyObjectives: This review aimed to identify the evidence for predictors of repetition of suicide attempts, and more specifically for subsequent completed suicide.Methods: We conducted a literature search of PubMed and Embase between January 1, 1991 and December 31, 2009, and we excluded studies investigating only special populations (eg, male and female only, children and adolescents, elderly, a specific psychiatric disorder) and studies with sample size fewer than 50 patients.Results: The strongest predictor of a repeated attempt is a previous attempt, followed by being a victim of sexual abuse, poor global functioning, having a psychiatric disorder, being on psychiatric treatment, depression, anxiety, and alcohol abuse or dependence. For other variables examined (Caucasian ethnicity, having a criminal record, having any mood disorders, bad family environment, and impulsivity) there are indications for a putative correlation as well. For completed suicide, the strongest predictors are older age, suicide ideation, and history of suicide attempt. Living alone, male sex, and alcohol abuse are weakly predictive with a positive correlation (but sustained by very scarce data) for poor impulsivity and a somatic diagnosis.Conclusion: It is difficult to find predictors for repetition of nonfatal suicide attempts, and even more difficult to identify predictors of completed suicide. Suicide ideation and alcohol or substance abuse/dependence, which are, along with depression, the most consistent predictors for initial nonfatal attempt and suicide, are not consistently reported to be very strong predictors for nonfatal repetition.Keywords: suicide, deliberate self-harm, suicide attempt, repetition, predictors